Q-Switching and mode-locking pulse generation based on passive techniques / Amri Ab. Rahman - Ab. Rahman, Amri (Institute of Graduate Studies, UiTM, 2015)
The field of fiber lasers and fiber optic devices has experienced a sustained rapid growth despite witnessing the infamous ‘telecom bubble burst’. All-fiber optic devices have inherent advantages of relatively low cost, compact design, light weight, low maintenance, and increased vibration tolerances. In this research, various new fiber lasers operating in Q-switching and mode-locking modes are proposed and demonstrated. At first, Q-switched Erbiumdoped fiber lasers are demonstrated using a homemade passive saturable absorber (SA) based on single-walled carbon nanotubes (SWCNTs) and graphene oxide films. For instance, with the use of a SWCNTs-Polyvinyl alcohol (PVA) SA, the laser has a multiwavelength output at 1533.5 nm region with a repetition rate of 13.1 kHz, pulse width of 7.2 μs and pulse energy of 21 nJ at the pump power of 64 mW. Two mode-locked EDFLs are also demonstrated using a homemade SA based on SWCNTs…